2019
DOI: 10.1136/lupus-2019-000336
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons in host defence and inflammatory diseases

Abstract: Type I interferons (IFN) can have dual and opposing roles in immunity, with effects that are beneficial or detrimental to the individual depending on whether IFN pathway activation is transient or sustained. Determinants of IFN production and its functional consequences include the nature of the microbial or nucleic acid stimulus, the type of nucleic acid sensor involved in inducing IFN, the predominant subtype of type I IFN produced and the immune ecology of the tissue at the time of IFN expression. When dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 153 publications
0
93
0
1
Order By: Relevance
“…The pDCs are specialized to rapidly produce large amounts of type I IFN, especially IFN‐α, in response to a broad range of viruses and some bacteria 19,20 . Type I IFN also has powerful immunomodulatory effects that can be deleterious and increase the risk for autoimmune disease in genetically predisposed individuals 21‐24 . For example, in systemic lupus erythematosus (SLE) a continuous type I IFN production by pDCs is triggered by an endogenous stimulator consisting of nucleic acid containing immune complexes (IC), for example autoantibodies and nucleic acid binding proteins 24‐27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pDCs are specialized to rapidly produce large amounts of type I IFN, especially IFN‐α, in response to a broad range of viruses and some bacteria 19,20 . Type I IFN also has powerful immunomodulatory effects that can be deleterious and increase the risk for autoimmune disease in genetically predisposed individuals 21‐24 . For example, in systemic lupus erythematosus (SLE) a continuous type I IFN production by pDCs is triggered by an endogenous stimulator consisting of nucleic acid containing immune complexes (IC), for example autoantibodies and nucleic acid binding proteins 24‐27 .…”
Section: Introductionmentioning
confidence: 99%
“…Type I IFN also has powerful immunomodulatory effects that can be deleterious and increase the risk for autoimmune disease in genetically predisposed individuals 21‐24 . For example, in systemic lupus erythematosus (SLE) a continuous type I IFN production by pDCs is triggered by an endogenous stimulator consisting of nucleic acid containing immune complexes (IC), for example autoantibodies and nucleic acid binding proteins 24‐27 . In addition, B cells can enhance the IFN‐α production by pDCs when stimulated by immune complexes consisting of small nuclear ribonucleoproteins and IgG isolated from SLE patients 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Advances in high-throughput screening of small-molecule inhibitors accelerate the discovery of new and more specific therapeutic options. The recognition of the key role of interferons in the JDM and SLE is an important development [21]. Anifrolumab, a potential new treatment targeting interferon receptor, just successfully completed a phase three clinical trial called Treatment of Uncontrolled Lupus via the Interferon Pathway.…”
Section: Update In the Managementmentioning
confidence: 99%
“…Furthermore, it has been reported that Lyp regulates type 1 interferon production after toll‐like receptor engagement in DCs . Type 1 interferon has pleiotropic effects, which include promoting the maturation of DCs into antigen‐presenting cells and B‐ and T‐cells survival, activation, and differentiation . In transplant setting type 1 interferon is involved in the induction of acute cellular graft rejection …”
Section: Demographic and Clinical Characteristics Of Corresponding LImentioning
confidence: 99%
“…10,11 Type 1 interferon has pleiotropic effects, which include promoting the maturation of DCs into antigen-presenting cells and B-and T-cells survival, activation, and differentiation. 12 In transplant setting type 1 interferon is involved in the induction of acute cellular graft rejection. 13,14 There are many SNPs in the gene of PTPN22.…”
mentioning
confidence: 99%